Analisis video: Teknik penerimaan dalam pertandingan sepak takraw semi-profesional - Yono, Topo; Susanto, Nugroho; Pavlovic, Ratko (Universitas Nusantara PGRI Kediri, 2025)
Reception analysis plays a crucial role in modern sports. One essential aspect of match analysis in Sepak Takraw is the reception technique. This study aims to analyze reception techniques through video recordings of semi-professional Sepak Takraw matches. The research employs a quantitative descriptive method using an indirect observation approach (video analysis). In its implementation, the researchers analyzed match footage to evaluate the receiving techniques used during the final match of the double event between the Jember and Malang teams at the 2023 East Java POMPROV. A purposive sampling technique was used to determine the research subjects, focusing on the receptions performed by both teams during the final match. The instruments in this study included video recordings and an observation checklist (receive analysis sheet), categorizing reception outcomes into successful receives (R1) and unsuccessful receives (R0). Data were analyzed using Microsoft Excel to calculate the number and percentage of successful and unsuccessful receptions. The descriptive analysis revealed that Jember had a higher success rate in both sets. In Set 1, Jember achieved a perfect reception success rate of 100%, while Malang reached 92.31%. In Set 2, Jember maintained the lead with 93.75%, whereas Malang recorded 90.56%. The conclusion indicates that the Jember team outperformed the Malang team in terms of reception success during the final match. These findings are expected to serve as a valuable evaluation tool for coaches aiming to enhance reception techniques in Sepak Takraw and for athletes seeking to improve their performance.